2017
DOI: 10.4081/jlimnol.2017.1601
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter dynamics in a savanna transition riparian zone: input of plant reproductive parts increases leaf breakdown process

Abstract: <p>The dynamics of coarse particulate organic matter (CPOM) drives the functioning of most low order freshwater ecosystems. We evaluated plant litter input, litterfall, leaf litter breakdown rates, and the aquatic invertebrate community over the course of one year in a stream situation in a transition zone between savannah and Atlantic forest. Total organic matter input (litter fall) was 335 g m<sup>-2</sup> yr<sup>-1</sup>, which was mainly composed of leaves (50%). Higher values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
5
0
1
Order By: Relevance
“…The richness and abundance of leaf litter input in the present study was higher in the rainy and transition seasons than during the dry season, as has been observed for other tropical riparian zones (Rezende et al 2016(Rezende et al , 2017a, confirming the marked seasonality of litterfall in tropical systems (França et al 2009, Gregório et al 2007, Wantzen & Mathooko 2008. Based on other studies of tropical streams in Brazil, leaf litterfall occurs mainly from August to October (França et al 2009, Gonçalves & Callisto 2013, 2017a, but our results identified input peaks occurred in October to December. This finding can be explained by two different mechanisms: the lateral input of the litter from the dry season by increased rainfall in the beginning of the rainy season; and the mechanical removal of green leaves from trees by the increased rainfall in October to December (late rainfall; Rezende et al 2016Rezende et al , 2017a.…”
Section: Fungal Community Structure and Leaf Litter Inputsupporting
confidence: 88%
See 1 more Smart Citation
“…The richness and abundance of leaf litter input in the present study was higher in the rainy and transition seasons than during the dry season, as has been observed for other tropical riparian zones (Rezende et al 2016(Rezende et al , 2017a, confirming the marked seasonality of litterfall in tropical systems (França et al 2009, Gregório et al 2007, Wantzen & Mathooko 2008. Based on other studies of tropical streams in Brazil, leaf litterfall occurs mainly from August to October (França et al 2009, Gonçalves & Callisto 2013, 2017a, but our results identified input peaks occurred in October to December. This finding can be explained by two different mechanisms: the lateral input of the litter from the dry season by increased rainfall in the beginning of the rainy season; and the mechanical removal of green leaves from trees by the increased rainfall in October to December (late rainfall; Rezende et al 2016Rezende et al , 2017a.…”
Section: Fungal Community Structure and Leaf Litter Inputsupporting
confidence: 88%
“…Based on other studies of tropical streams in Brazil, leaf litterfall occurs mainly from August to October (França et al 2009, Gonçalves & Callisto 2013, 2017a, but our results identified input peaks occurred in October to December. This finding can be explained by two different mechanisms: the lateral input of the litter from the dry season by increased rainfall in the beginning of the rainy season; and the mechanical removal of green leaves from trees by the increased rainfall in October to December (late rainfall; Rezende et al 2016Rezende et al , 2017a. The time-lag for the peak of leaf litter input (by one or two months) in the present study may indicate the need for increased rainfall to start leaf senescence or to make the leaves more susceptible to mechanical removal by rainfall, in comparison to other tropical systems.…”
Section: Fungal Community Structure and Leaf Litter Inputmentioning
confidence: 39%
“…The mean of VI (24 g.m -2 month -1 ) occupies the low range reported for both Brazilian savanna (24 -42 g.m -2 month -1 in Tonin et al 2017;Rezende et al 2017a) and tropical riparian zone (9 -234 g.m -2 month -1 in (Zhou et al 2007, Kleba Lisboa et al 2015. The LI (mean of 49 g.m -2 month -1 ) was twice bigger than mean VI, indicating that indirect inputs are the major energy source.…”
Section: Aom Dynamicsmentioning
confidence: 78%
“…Higher precipitation increased the litter breakdown rates, that could be explained by: (1) an increase in litter fragmenta- tion due to physical abrasion (higher water washing force and stream discharge) (Graça et al 2015, Wantzen and Wagner 2006, Wootton et al 2018; or (2) an increase in the activity and exploration of the decomposer community due to higher litter quality input (Gessner et al 2010, Rezende et al 2017a. As example, Rueda-Delgado et al (2006) showed that abiotic factors such as physical abrasion drove the leaf litter breakdown in the Amazonian floodplain.…”
Section: Ecological Process and Decomposer Community Interactionsmentioning
confidence: 99%
“…A potentially higher nutritional quality of such reproductive plant parts compared to leaves may favor rapid decomposition of the litter supplied to tropical streams. However, the fruits of Clitoria fairchildiana and other species in the managed AFS we investigated may not provide a high-quality nutritional resource ( Rezende et al, 2017c ), and we do not currently have data to evaluate the consequences for litter decomposition.…”
Section: Discussionmentioning
confidence: 99%